Synthesis and Morphology control of TiO2 Nanostructure via Hydrothermal method for application as Electrodes in dyesensitized solar cells - Noor, A.M.; Radiman, S.; Ming, H.N.; Ngee, L.H.; Yarmo, M.A.; Rahim, S.; Ahmad, S.I.; Shamsudin, S.A.; Sajab, M.S. (2013)
Nano structured TiO2 with different sizes and shapes were synthesized through the hydrothermal method using TiO2 nanoparticles powder as the precursor. Hydrothermal system that is easy, inexpensive and free-templates at 180 degree Celsius temperature treatment, the influence of alkaline medium with the addition of NaOH and KOH on the size, morphology and photovoltaic properties of TiO2 nano structures have been studied. Samples were characterized by transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX) while the ability of the dye sensitized solar cells (DSSC) were measured using Potentiostat Gamry Series G-300. The study by using different alkaline agent (NaOH and KOH) clearly influence the morphology of TiO2 and the dye sensitized solar cells consisting of TiO2 nano rod structure shows the best capability with an open circuit voltage (Voc) of 416.8 mV, a short circuit current density (Jsc) of 0.169 mA/ cm2 and a conversion efficiency (η) of 0.0232 % under AM 1.5 xenon lamp illumination